New species of the genus Corynoneura Winnertz (Diptera, Chironomidae) from Brazil - Wiedenbrug, Sofia; Trivinho-Strixino, Susana (Zootaxa, 2011)
Seven new species of the genus Corynoneura Winnertz from small streams in the Atlantic Forest are described; Corynoneura fortispicula sp. n., Corynoneura hermanni sp. n., Corynoneura mediaspicula sp. n., Corynoneura mineira sp. n., Corynoneura septadentata sp. n., Corynoneura sertaodaquina sp. n., Corynoneura unicapsulata sp. n., as male, female, pupa and larva. Diagnosis and drawings of other two morphotypes based on female, pupa and larva are given. Larvae were collected from rocks, leaves and debris near the water surface and were reared. Males here described are defined by the phallapodeme sclerotized on posterior margin, females usually have labia fused as funnel.